GE_GERICHTE P/9122/2016 vom 7. Dezember 2018 - GE Cour de justice (2018)
VIOLATION DE DOMICILE ; LÉSION CORPORELLE GRAVE ; ARME(OBJET) ; SCHIZOPHRÉNIE ; TENTATIVE(DROIT PÉNAL) ; LÉGITIME DÉFENSE ; MESURE THÉRAPEUTIQUE INSTITUTIONNELLE ; EXPULSION(DROIT PÉNAL) | CPP.339.al2; CPP.339.al3; CPP.339.al4; CPP.399.al4; CP.186; CP.122; CP.12.al2; CP.22; CP.15; CP.47; CP.49.al1; CP.56.al1; CP.59.al1; CP.59.al2; CP.59.al3; CP.57.al2; CP.66a.al1.letb; CP.66a.al2